P210 Long-term outcome of very early onset inflammatory bowel disease associated with primary sclerosing cholangitis: a multicenter study from the Pediatric IBD Porto Group of ESPGHAN. (30th January 2023) - Catassi, G; D'Arcangelo, G; Norsa, L; Bramuzzo, M; Hojsak, I; Kolho, K L; Romano, C; Gasparetto, M; Di Giorgio, A; Hussey, S; Yerushalmy-Feler, A; Turner, D; et al.
Abstract: Background: Primary sclerosing cholangitis related to inflammatory bowel disease (PSC-IBD) diagnosed under the age of 6 years (i.e., VEO-IBD) may have unique characteristics and disease course. We aimed to analyze the characteristics and natural history of children with VEO PSC-IBD and compare them to children diagnosed with PSC-IBD at an older age. Methods: This was a multicenter, retrospective, study evaluating patients diagnosed with both IBD and PSC before (VEO-PSC-IBD) or after the age of 6 years (PSC-IBD), followed at 14 centers affiliated with the Porto IBD Interest group of ESPGHAN. Demographic, clinical, laboratory, endoscopic, and imaging data were collected at baseline and every six months thereafter for a minimum follow-up of 12 months. IBD-related (clinical remission, need for systemic steroids, therapy escalation and surgery) and PSC-related outcomes (biliary and portal hypertensive complications, need for treatment escalation and liver transplantation, cholangiocarcinoma, and death) were analyzed at 1, 3, and 5 years. Results: A total of 69 children with both IBD and PSC were included: 28 with VEO PSC-IBD [median age 5.2 (3.7-5.9) years, 21 UC (75%), 4 IBDU (14%) and 3 (15%) CD] and 41 with PSC-IBD [median age 15.7 (13.3-16.9) years, 34 UC (83%), 6 IBDU (1.5%) and 1 (0.2%) CD]. IBD was diagnosed prior to PSC in 28 of the 69 patients (40%), simultaneously in 30 (43%), and after PSC in 11 (16%), with no significant differences between VEO PSC-IBD and PSC-IBD. Most patients with UC presented with extensive disease at diagnosis (89% in VEO PSC-UC vs. 89% in PSC-UC, p = 0.72). Both groups presented most often with mild intestinal disease at diagnosis (mean PUCAI of VEO IBD-PSC 34±16, vs 31±19 of IBD-PSC, p=0.11; mean PCDAI 31±33 vs. 21±27, respectively, p=0.14). A higher number of VEO-IBD-PSC patients were diagnosed with autoimmune sclerosing cholangitis than older children [24 (86%) vs. 27 (66%) PSC-IBD, p=0.04], whereas no other differences were found for PSC-related variables. During follow-up, no significant differences were found in major IBD outcomes. The risk of developing biliary strictures and escalating therapy to vancomycin from ursodeoxycholic acid was lower in the VEO-PSC-IBD group (Figure 1 and 2, Log-rank p=0.02 and p=0.02), while no difference was found for portal hypertension and liver transplantation at 5-year follow-up. No cases of cholangiocarcinoma or death were reported. Conclusion: IBD-PSC has similar baseline characteristics whether diagnosed as VEO-IBD or thereafter. However, a milder disease course in terms of biliary complications and the need for PSC-related therapy escalation, with an overall mild intestinal disease at presentation in all patients, characterize this specific subcohort of patients.